Biocoagulant from bacteria: a review - Hassan, Hamidah; Alam, Md. Zahangir; Al-Mamun, Abdullah (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Coagulants are used to remove turbidity from raw water for potable usages. Chemical coagulants are widely used in the water treatment and other industries due to less cost and rapid production benefits. However, the negative effects of these chemical coagulants should not be neglected to gain the economic benefit only. Therefore, the researchers are working on to discover efficient and economical coagulants from biomaterials. This paper presents the progress in discovering bio-coagulants from bacterial organisms. It is revealed that significant amount of works have been done in the past. However, commercially viable coagulants from bacteria are yet to be marketed. With the advent of new and modern biotechnologies and advances in genetic engineering, the researchers are hopeful to discover or develop commercially viable, safe and environment-friendly bio-coagulants from bacteria.